10 Pharmacodynamic profiles of aspirin versus dual-pathway inhibition with either aspirin or clopidogrel among patients with stable atherosclerotic disease. (8th December 2021) - Galli, Mattia; Franchi, Francesco; Rollini, Fabiana; Been, Latonya; Jaoude, Patrick; Rivas, Andrea; Zhou, Xuan; Jia, Sida; Maaliki, Naji; Lee, Chang; Pineda, Andres; Suryadevara, Siva; et al.
Abstract: Aims: Inhibition of thrombin-mediated signalling processes using a vascular dose of rivaroxaban in adjunct to single antiplatelet therapy, known as dual-pathway inhibition (DPI), reduces atherothrombotic events in patients with stable atherosclerotic disease. However, there is limited data on the pharmacodynamic (PD) effects of this strategy. Methods: This investigation was conducted in selected cohorts of patients ( n  = 40) with stable atherosclerotic disease enrolled from a larger prospective, open-label, parallel-group PD study who were treated with either aspirin, aspirin plus rivaroxaban 2.5 mg/bid or clopidogrel plus rivaroxaban 2.5 mg/bid. Multiple PD assays providing a comprehensive assessment of markers of thrombosis were used. The primary endpoint was the comparison between groups of platelet-mediated global thrombogenicity by light transmittance aggregometry (LTA) following stimuli with collagen-related peptide + adenosine diphosphate + tissue factor (CATF). Results: There were no differences in the primary endpoint between aspirin vs. aspirin plus rivaroxaban 2.5 mg/bid ( P  = 0.110), aspirin vs. clopidogrel plus rivaroxaban 2.5 mg/bid ( P  = 0.611) or aspirin plus rivaroxaban 2.5 mg/bid vs. clopidogrel plus rivaroxaban 2.5 mg/bid ( P  = 0.315). Rivaroxaban-based treatments significantly reduced markers of thrombin generation (peak thrombin and thrombin velocity index). Clopidogrel-based treatments reduced markers of P2Y12 signalling (LTA ADP 20 max and VerifyNow). Aspirin-based treatments reduced markers of markers of cyclooxygenase-1 activity (LTA collagen). Conclusions: Compared with aspirin alone, DPI with either aspirin or clopidogrel might provide superior ischaemic protection by targeting pathways alternative to those affected by antiplatelet agents with only a moderate trade-off in bleeding as supported by similar platelet-mediated global thrombogenicity between treatments.